Joe Biden Intervention in the Russian Invasion Effort Against Ukraine - Alunaza SD, Hardi; Shafitri, Desy Nur; Ernianda, Annisa; Putri, Anggi (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2022)
The protracted conflict between Russia and Ukraine since 2014 has reached an unpredictable peak of tension. The military invasion of Russia on February 24, 2022, overwhelmed Ukraine in the face of attack. Randomly bombed facilities caused thousands of civilians to lose their homes and lives. Initially, this conflict was caused by the seizure of the territory of the Crimean Peninsula. The conflict spread to the United States and the North Atlantic Treaty Organization (NATO), ending in a difficult situation to control. Primarily when the United States officially provided military assistance to Ukraine during the conflict. In explaining this article, the author will use the Infra State-War Theory, the Concept of Military Intervention, and the Rational Actor Model Theory with a qualitative approach and descriptive research methods. This study's results aim to analyze the continuation of the conflict between Russia and Ukraine. The author will look at the evolution of the intervention of the United States in the era of Joe Biden's leadership in three phases of discussion. First, this article will elaborate on the origin of the conflict over the territory of the Crimean Peninsula. Second, it describes the interventions that have been carried out by the United States before. Third, this article will explain and analyze how the United States intervened during the leadership of Joe Biden.